Pelatihan dan Pendampingan Operasional Mesin Bubut Bagi Karyawan di Kawasan Industri Logam Morowali - Setiawan, Angga Tegar; Alfafa, Abduh Malik; Putra, Eriek Aristya Pradana; Wijayanto, Hendi Lilih; Nugroho, Vincentius Sulistyoaji; Saputra, Adityo Tri; Kamaruddin, Kamaruddin (Politeknik ATI Padang, 2024)
In the increasingly advanced and dynamic world of the manufacturing industry, the need for a skilled and qualified workforce is becoming increasingly important. One of the key skills required in the industry is the ability to operate a lathe effectively and efficiently. Lathes are used to shape and smooth workpieces by rotating the workpiece against a stationary tool. These machines enable precise and high-quality manufacturing processes, so employees need to master the correct and efficient operation of lathes. However, there is still a problem with employees who are not skilled enough to operate lathes in companies in the Morowali metal industry area. This condition can certainly hamper the productivity and efficiency of the company, and have an impact on the quality of the products produced. So, it is necessary to conduct training and mentoring to improve their knowledge and skills. Training is carried out using several methods, namely surveys through interviews to determine the appropriate type of training. Providing material to improve knowledge using the lecture method. Direct observation to train participants' skills in operating the lathe. Evaluation of training to measure the level of achievement. The evaluation results obtained an average pre-test score of 54.3 and a post-test of 84.6. There was an increase of 30.7 points after the participants participated in the training activities. Thus, the training activities showed success in improving employees' knowledge of lathe operation. In addition, each employee also showed skills in completing the job sheet that had been given. So, the training carried out provides various benefits for employees in developing careers and for companies in increasing their productivity.